The role of anifrolumab in reshaping the treatment landscape of extra-renal systemic lupus erythematosus - Fulvia Ceccarelli; Matteo Piga; Alessandra Bortoluzzi; Laura Coladonato; Micaela Fredi; Daniele Mauro; Chiara Tani; Luca Iaccarino (Reumatismo)
Objective. Systemic lupus erythematosus (SLE) is a multifaceted autoimmune disorder that typically requires management with immunosuppressive and anti-inflammatory treatments. The 2023 guidelines of the European Alliance of Associations for Rheumatology now recommend lowering maintenance glucocorticoid doses to ≤5 mg/day to reduce long-term health risks, a decrease from the previous 7.5 mg/day threshold set in 2019. To help achieve these reduced doses, early initiation of biologic therapies is suggested, even before conventional immunosuppressants. Belimumab and anifrolumab, the biologics currently approved for SLE treatment, have shown greater efficacy than placebo in clinical trials and similar safety profiles, supporting their use in achieving remission and enabling glucocorticoid tapering or discontinuation. This review evaluates the role of biologics, especially anifrolumab, in treating extra-renal SLE in Italy, using clinical scenarios to illustrate situations where early anifrolumab therapy could be beneficial.